Deposition and slag flow modeling with SPH for a generic gasifier with different coal ashes using fusibility data. (15th May 2016) - Kurowski, M.-P.; Spliethoff, H.
Highlights: The slag flow of coal ash is simulated with the Smoothed Particle Hydrodynamics method as a novel approach. Two different coal sorts are examined in this work. The slag flow behavior is adapted to experimental ash fusion data. The ash with a higher viscosity builds up a thicker slag layer. The new simulation method covers the complete melting range of slag. Abstract: In the simulation of entrained flow reactors for gasification processes, not only the gasification reactions are of interest, but also an understanding of the behavior of the ash particles is crucial since the impact on the operating conditions due to slagging cannot be neglected. In this work a new approach for modeling slagging processes was developed. Most of the conventional models for slag flows are based on an Eulerian approach, but a Lagrangian approach could give a better representation of the free surfaces and the multiphase flow. Therefore, the particle method SPH (Smoothed Particle Hydrodynamics) was chosen to model the slag flow. This method offers advantages over the conventional models for slagging, especially in the field of multiphase simulations. Free surfaces are naturally represented and even break-ups of the slag deposit can be simulated without numerical instability. Here the hydrodynamic SPH method is adjusted by taking into account the non-newtonian behavior of the partly solidified slag, depending on the coal ash composition, temperature and thermochemical properties. The latter was achieved by using FactSage. The interface between liquid and solid slag is represented by a multiphase model. The deposition rate was given as an input parameter to determine the deposition build-up and subsequently the melting process was calculated. The deposition and slag-flow happens simultaneously. To model the complex flow behavior of partly molten slag, the ash fusion test results for two specific coal types were used to determine duration and form of the melting process. Combined with the FactSage data, the slag flow was simulated for a generic gasifier wall and the slag build-up of the two different coal ashes was compared between each other.